Developing Students’ Writing Ability through Google Application - Bahnar, Siti Hardiyanti (ELT Worldwide: Journal of English Language Teaching, 2021)
This study aims to find out writing descriptive text ability of the tenth grade students of SMA 1 Barru by using Google application. Based on the information of the EFL teacher of SMA 1 Barru, she said that 70% of the tenth grade students of SMA 1 Barru have low ability to write in English descriptive text. In regard to this problem, the researcher intended to develop the students’ writing ability. This research applied a pre-experimental method with one group pretest and posttest design and used cluster random sampling technique, which just one class was taken as sample. In collecting data, the researcher used writing test through Google application. The result of the data analysis was showed that the students’ writing descriptive achievement developed after treatment through Google application. Based on the result of data analysis, the researcher concluded that the use of Google application was effective in developing the students’ writing descriptive text ability. The students do not only consume their own writing, but they can share to other via online.